IPMs solving major reliability issues in automotive applications [intelligent power module] - HUSSEIN, K. H; MAJUMDAR, G; YOSHIDA, S; MAEKAWA, H (2004 proceedings of the 16th International Symposium on Power Semiconductor Devices and ICs : 24-27 May 2004, 2004)
In automotive applications, particularly the newly emerging hybrid electric vehicles (HEV), the high power ratings (10-100 kW peak), together with the high temperature associated with the engine room, subject the IPM (intelligent power module) to severe thermal operating conditions. Therefore, in addition to the well known requirements of improved IPM electrical characteristics and optimized system cost-performance (functional integration), reliability and durability become very important factors in HEV applications. This paper highlights the IPM system model for HEV: the intelligent integrated power drive unit (IPU) which, through efficient power chips, built-in detection, protection, and optimized package layout, pushes forward more functional integration and satisfies the HEV reliability requirements. The IPU thermal management (in terms of package layout and on-chip temperature sensing) and short-circuit protection circuits are introduced as examples.